The Influence Of Work Environment, Work Motivation, Work Skills On Employee Performance With Job Satisfaction As An Intervening Variable At PT. Sudira Makmur Indonesia - Maria Magdalena Br Manurung; Rasinta Ria Ginting; Cut Fitri Rostina; Wiliam Wiliam (Jurnal of Management and Social Sciences, 2025)
Human resources are one of the factors that greatly influence the development of a company. The success or failure of achieving organizational goals all depends on the ability of Human Resources or employees in the organization. These human resources are required to continue to be able to develop their abilities proactively in the organization. This study aims to determine whether the work environment, work motivation, work competence affects employee performance with job satisfaction as an intervening variable at Pt. Sudira Makmur Indonesia. Research was conducted on 32 employees using saturated sampling techniques. The data collection techniques used were primary data in the form of questionnaires and secondary data obtained through documentation studies. The data analysis technique uses quantitative data processed with the SPSS version 20 program, namely at the analysis stage of the data quality test, classical assumption test, hypothesis testing, determination coefficient test (R2) and path analysis. The results obtained in this study indicate (1) There is a significant influence between work environment variables on employee performance, (2) There is no significant influence between work motivation variables on employee performance, (3) There is a significant influence between work competency variables on employee performance, (4) There is no significant influence between work environment variables on job satisfaction, (5) There is a significant influence between work motivation variables on job satisfaction, (6) There is no significant influence between work competency variables on job satisfaction, (7) There is a significant influence between employee performance variables on job satisfaction, (8) Work environment variables through employee performance have a significant effect on job satisfaction, (9) Work motivation through employee performance has no effect on job satisfaction, (10) Work competence through employee performance has a significant effect on job satisfaction.